The Roles of lncRNA in Cutaneous Squamous Cell Carcinoma - Wang, Yujia; Sun, Bensen; Wen, Xiang; Hao, Dan; Du, Dan; He, Gu; Jiang, Xian (Frontiers in Oncology, 2020)
Cutaneous squamous cell carcinoma derived from keratinocytes and was the second most non-melanoma skin cancer. Cutaneous squamous cell carcinoma developed rapidly, which was also the leading cause of death in non-melanoma cancers. Lymph node metastasis occurred in 5% of cSCC patients and some patients may even metastasize to viscera. Patients with regional lymphatic metastasis or distant metastases had a less than 20% 10-year survival rate, indicating the substantial challenge in treating advanced and metastatic cSCC. In this review, we summarized the role of lncRNA in cutaneous squamous cell carcinoma to make a better understanding of mutations in cSCC and lay the foundation for effective target therapy of cSCC.